Norm estimation for pre-Schwarzian and Schwarzian derivatives of some univalent functions - Wu, Xiaobin; Zhu, Wanghao (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 Our purpose is to obtain estimates for the norms of Schwarzian and pre-Schwarzian derivatives of strongly starlike functions and strongly convex functions of order α and type β. In addition, we present an example of a function f S^*(α, β) that cannot be k-quasiconformally extended for any k < α(1 - β).